(untitled) (African Journal of Biomedical Research, 2023)
This study evaluated the effects of formulated ketogenic diet (KG) and coconut (hot and cold pressed) oils on male obese Sprague Dawley rats. Thirty rats weighing between 180-200g were divided into six groups of five rats each. Group 1 was fed with the standard rat chow (normal control) while groups 2 to 6 were fed with high fat diet (HFD) for 4 weeks to induce obesity. Thereafter, the obsessed animals were treated for another 2 weeks on the following formulated diets: group 2 was maintained on HFD only, groups 3 to 6 were concomitantly placed on cold-pressed coconut (CPC) oil diet (HFD+CPC), hot-pressed coconut (HPC) oil diet (HFD+HPC), KG diet (HFD+KG) and orlistat (FATNIL®) (20mg/kg), an established anti-obesity agent. At the expiration of 4 weeks, there were significant (p < 0.05) gain in body weight, body mass index (BMI) and adiposity index (AI). Also, there were increase in low density lipoprotein (LDL), total cholesterol (TC) and triacylglycerol (TAG) levels in the HFD fed groups. However, after 2 weeks of intervention treatment, there were significant (p < 0.05) reduction in the body weights, BMI, AI, HDL cholesterol and TC levels of the rats in the HFD+CPC, HFD+KG and orlistat treated groups. The CPC oil, KG and orlistat diet treated groups showed marked decrease in serum transaminases activities, catalase activity, superoxide dismutase (SOD) activity and hepatic malondialdehyde (MDA) level. This study revealed that CPC oil and short term consumption of KG diet demonstrated a lipid-lowering effect and reduction in indicators of obesity.